Hubungan Media Sosial dalam Pembentukan Karakter Anak - Erni Ratna Dewi (ILIN Institute, 2020)
Children are valuable assets for parents, children become a reflection of how their parents themselves. Social media as a social structure that comes from individuals and organizations that comes from individuals and organizations that are bound by the similarity of users. The research method used is a combination of qualitative and quantitative descriptive or commonly reffered to as mixed methods. Data sources consist of primary and secondary data. The population in this study were parents of class IV to class VI at 4 Elementary Schools. The sampling technique used was random sampling method which was obtained by 124 respondents. Data analysis techniques are descriptive statistics and Chi-Square analysis. The results found that the social media is determined by the application, content and effects caused in the formation of children's characters. Social media applications have a relationship in shaping the character of children. The application is tailored to the needs of children such as applications than can help the child's learning process, increase their knowledge and socialization. Social media content has a relationship is shaping the character of children. The content is tailored to the needs of children who sould be a concern of parents to provide supervision of what children do with gadgets. The effect of social media has a relationship in the formation of children's character. This shows that social media as a whole has a bad effect on the formation of childred's characters. This is because social media not only has positive values, but also negative ones depending on the application and the content they have.